1992
DOI: 10.2466/pms.1992.74.2.627
|View full text |Cite
|
Sign up to set email alerts
|

Abortion Attitudes, 1984-1987-1988: Effects of Item Order and Dimensionality

Abstract: The comparability of surveys is often hampered by differences in the item order of presentation. The major focus of the present study was to investigate whether a general item or a specific item at the beginning of the questionnaire would affect the endorsement as well as the scalability of a set of attitude items. By using a quasi-A-B-A experimental design for the six abortion items that appeared in the Edmonton Area Survey for the years 1984, 1987, and 1988, we found that the order of presentation of the ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…Of these, three were health-related randomised controlled trials, [107][108][109] nine were randomised trials on nonhealth topics [110][111][112][113][114][115][116][117][118] and two were health-related historically controlled studies. 119,120 Nine involved interviewer-adminis-tration (in eight cases by telephone), four were postal surveys and one a self-completion survey conducted in a workplace. As with those on question wording, the quality of the studies was generally high, although none reported explicitly that sample size calculations were based on a power calculation.…”
Section: Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, three were health-related randomised controlled trials, [107][108][109] nine were randomised trials on nonhealth topics [110][111][112][113][114][115][116][117][118] and two were health-related historically controlled studies. 119,120 Nine involved interviewer-adminis-tration (in eight cases by telephone), four were postal surveys and one a self-completion survey conducted in a workplace. As with those on question wording, the quality of the studies was generally high, although none reported explicitly that sample size calculations were based on a power calculation.…”
Section: Identified Studiesmentioning
confidence: 99%
“…• general context effects 108,110,112,114,115,117,118,120 • ordering of general versus specific questions 107,111,117,119 • contiguous versus non-contiguous questions 113,116 • ordering of disease-specific versus generic health status instruments. 109…”
Section: Identified Studiesmentioning
confidence: 99%
“…It is also noteworthy that loss of function of Fgfr2 in the mouse uterus leads to luminal epithelial stratification and peri-implantation pregnancy loss ( Filant et al, 2014 ). Moreover, Mmp7 and Wnt7b are upregulated upon E2 stimulation and participate in the re-epithelialization of the endometrium and implantation process, respectively ( Russo et al, 2009 ; Tenvergert et al, 1992 ; Hayashi et al, 2009 ). In accordance with the phenotype of hyperproliferative endometrial epithelium during early pregnancy, observed in SMAD1/5 cKO mice, we demonstrated that the suppression of key E2-responsive genes, such as Fgfr2 and Mmp7, by SMAD1/5 maintains the precise balance between E2 and P4.…”
Section: Resultsmentioning
confidence: 99%
“…It is also noteworthy that loss of function of Fgfr2 in the mouse uterus leads to luminal epithelial stratification and peri-implantation pregnancy loss 62 . Moreover, Mmp7 and Wnt7b are up-regulated upon E2 stimulation and participate in the re-epithelialization of the endometrium and implantation process, respectively [64][65][66] .…”
Section: Direct Target Genes Of Smad1 and Smad5 Maintain The Homeosta...mentioning
confidence: 99%